Ator A Zan Adua (Christian Traditional Rulers) and Tiv Culture in the 21st Century - Adega, Andrew Philips; Degarr, Daniel Terna; Terkura, Myom (International Journal of Culture and History, 2024)
The chieftaincy and traditional rulership institution is dynamic and one of the most enduring legacies from traditional African societies. Until the coming of the colonialists, the traditional institution led by chiefs, emirs, obas, Ezes, etc performed legislative and judicial functions as well as political, religious, social and economic roles etc. The chieftaincy and traditional rulership institution among the Tiv was not organised in a systematic manner until the creation of the Tor Tiv stool in 1946. With several reformations, the chieftaincy institution has taken a definite stage in Tiv society. However, the problem of the study has to do with the fact that there has arisen in the Tiv chieftaincy scene; the ator a zan adua (Christian traditional rulers) who rather than protect and preserve Tiv cultural heritage are in the vanguard of the corrosion of a culture they had taken an oath to protect and preserve. If prompt action is not taken by the Tiv, their culture would soon disappear as these ator a zan adua have “churchmentised” and Christianised Tiv culture. As scholars of Tiv History, Religion and Culture, the researchers are alarmed at this cultural imperialism being perpetrated by Tiv traditional rulers. The study adopts the historical, descriptive and evaluative methods. In data collection, the primary and secondary methods have been adopted. In the primary source, oral interviews and the observation methods have been used; whereas in the secondary sources of data collection, documented sources from books, journal articles, newspapers and e-sources have been employed. The study established that by the orientation of ator a zan a dua as Christians, they are on the verge of completely supplanting Tiv culture with a foreign one. The study noted that culture gives an identity to a group of people and without it, they cannot be defined. In view of this challenge, the study made various suggestions as means of preserving and sustaining Tiv cultural heritage for generations yet unborn. One of these suggestions is that traditional rulers in Tiv be made to take their oath of office by Swem (the Tiv symbol of justice) so that when they renege on their oath, they would immediately bear the consequences (death by swollen stomach, limbs and severe headache). The study concluded that Tiv culture must not be sacrificed on the altar of Christianity by anybody not even the ator (traditional rulers).